The Epilepsies of Rett Syndrome in Indonesia - E. S. Herini; Sunartini H; I. Mangunatmadja; Purboyo S; Hardiono D. Pusponegoro (Paediatrica Indonesiana, 2005)
Objective This study aimed to evaluate various types of sei-zures, EEG findings, and last evolution of epileptic seizures foundin children with Rett Syndrome (RTT).Methods A case series of ten female subjects from Sardjito Hos-pital, Yogyakarta; Cipto Mangunkusumo Hospital, Jakarta; andHasan Sadikin Hospital, Bandung from February 2001-April 2004.Diagnosis of RTT was established using necessary and support-ive criteria by the RTT Diagnostic Criteria Work Group and epi-lepsy was diagnosed according to clinical and EEG findings.Results The age during initial diagnosis of RTT ranged from 2years 6 months - 10 years 2 months (average: 4 years 6 months).The diagnosis of epilepsy, on the other hand, was establishedfrom 2 years - 5 years 10 months (average: 3 years 8 months).All subjects (10/10) had abnormal EEG results. Eight out of tenhad epileptiform discharge; the remaining had slowing backgroundactivity. The average age of initial seizure onset was 18 months.Five were diagnosed as epileptic subjects. Febrile convulsionswere the most common initial seizure. General tonic clonic sei-zure was major type of seizure which manifested in 2 subjects.Conclusion All EEG results showed abnormality, although sei-zure did not appear. Five out of ten subjects experienced epi-lepsy